A theory of the skill-performance relationship - Iso-Ahola, Seppo E. (Frontiers in Psychology, 2024)
The skill-performance relationship is a cornerstone of a meritocratic society. People are selected to schools, colleges and jobs based on the premise that more skillful individuals perform better.Scientific understanding of the skill-performance relationship demands that the effect of skill on performance is objectively assessed without subjective, social, and political considerations. One of the best arenas for this analysis is sports. In many sports settings, the skill-performance relationship can objectively be examined at the behavioral, technical, psychological, and neurological levels. This examination reveals that skill and performance are inextricably intertwined. Skill affects and is affected by performance, and performance defines skill and is determined by skill. To disentangle the previously confusing and interchangeable use of these key constructs, the paper presents a theoretical model specifying that ability and effort have their own direct effects on performance, as well as indirect effects on performance through skill possession and skill execution in cognitive and physical domains of human performance. Thus, ability and skill are not the same. Although skill is a key determinant of performance, recent theory and research suggests that successful performers are successful not just because of their skills per se, but because they take advantage of their skills by creating more occurrences of momentum, making them last longer and using them to bounce back faster from streaks of unsuccessful performance. Thus, momentum is an important mediator of the effects of skill on performance.